2015
DOI: 10.1080/00140139.2015.1076528
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomics standards and guidelines for computer workstation design and the impact on users’ health – a review

Abstract: This paper presents an overview of global ergonomics standards and guidelines for design of computer workstations, with particular focus on their inconsistency and associated health risk impact. Overall, considerable disagreements were found in the design specifications of computer workstations globally, particularly in relation to the results from previous ergonomics research and the outcomes from current ergonomics standards and guidelines. To cope with the rapid advancement in computer technology, this arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 75 publications
5
59
0
1
Order By: Relevance
“…An important issue regarding visibility of computer screen tasks is the font size in relation to the visual distance. The scientific literature includes several recommendations for suitable viewing angles and distances, some of them conflicting [40]. According to the much-referred to international ISO standard [41], the visual angel should be about 22 arcmin, i.e., approximately 4 millimeter at a visual distance of 70 centimeter.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…An important issue regarding visibility of computer screen tasks is the font size in relation to the visual distance. The scientific literature includes several recommendations for suitable viewing angles and distances, some of them conflicting [40]. According to the much-referred to international ISO standard [41], the visual angel should be about 22 arcmin, i.e., approximately 4 millimeter at a visual distance of 70 centimeter.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…They further demonstrated that not only the median nerve but also tendons were significantly larger in the dominant hand of smartphone users than in the dominant hand of nonusers. Although ergonomic standards and guidelines for computer workstations are readily available today, they usually are not compatible with the current setups required by mobile technologies . Future studies investigating ergonomic designs for handheld electronic devices, such as single hand use, are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The physical work environment influences both worker well‐being and organizational performance 17,18 . Whether they work at a central facility, mobile site, home office, or in a different country or time zone, future workers across occupations and industries will continue to need access to ergonomically designed workstations and work tools, personal protective equipment (PPE), and hazard‐free work environments 19 . Exactly how safe working environments will be provided and maintained as the physical boundaries of work become increasingly fluid, however, remains unclear.…”
Section: Cdc/niosh Future Of Work Initiative Priority Topicsmentioning
confidence: 99%